Unravelling the anthropogenic pathways of phosphorus in the food production and consumption system of Bangladesh through the lens of substance flow analysis. (30th July 2019) - Roy, Bidhan Bhuson; Biswas Chowdhury, Rubel; Baroi, Amit Robert; Rahman, Shupa; Powers, Stephen M.; Milne, Nick; Sujauddin, Mohammad
Abstract: Phosphorus (P) is central to food production. Current understanding about the global phosphorus system is dominated by studies in wealthier nations where soil fertility, fertilizer supply chains, and agronomic tracking have long been established. In contrast, developing nations are experiencing major agricultural transitions and the associated phosphorus flows remain a significant knowledge gap. We compiled and analyzed several years of recent agricultural datasets for Bangladesh, currently the eighth most populous nation, using substance flow analysis for phosphorus. From 2000 to 2016, rice production increased by >50% and remained the dominant crop with remarkably higher phosphorus flow (49.96 kt in 2016) than all other crops. Phosphorus content of livestock products in 2016 exceeded 6.00 kt, more than double in the year 2000, driven primarily by phosphorus in milk and secondarily in meat/eggs. These agricultural changes coincided with a doubling of national phosphorus fertilizer consumption since 2000, a fourfold increase since the global food crisis (2009), and a pronounced rise in the phosphorus import dependency ratio, which was the highest among all countries compared. In turn, during 2010s fertilizer phosphorus use exceeded phosphorus as food + feed production leading to soil phosphorus accumulation, and loss as burned manure became one of the largest phosphorus flows in the entire system, equivalent to half of fertilizer use. This dramatic reconfiguration of the Bangladesh phosphorus system illustrates an important case of agricultural expansion and intensification that is still playing out, with similar situations occurring in developing nations where population growth rates are high, and access to commercial fertilizers has risen.